Academic Stress in Health Behavior in University Students of Metropolitan Lima - Arpi Barazorda, Evelyn Naire (2024)
University students are commonly subjected to stressful situations that directly and indirectly impact the development of healthy behaviors. This research aims to evaluate how academic stress affects the health behavior of students at a university in Metropolitan Lima. A non-experimental, quantitative, and correlational study was applied, using the Health Behavior Questionnaire for young university students (CEV-JU) and the SISCO-21 Academic Stress Inventory, applied to 708 students in which the sample was intentional non-probabilistic. The results showed that stress symptoms, stressors, and coping strategies were significantly associated with general health behavior and some dimensions. Likewise, it was found that the most significant predictors of health behavior outcomes were the coping strategies and the symptom dimension. These findings highlight the importance of designing and implementing programs and interventions aimed at adequately managing stress to promote healthy habits among university students.